2020
DOI: 10.1016/j.whi.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Birth Mode after Primary Cesarean among Hispanic and non-Hispanic Women at One U.S. Institution

Abstract: Background: Despite a lower percentage of primary cesareans than non-Hispanic White and Black women, Hispanic women in the United States had the highest rate of repeat cesarean deliveries (RCD) in 2016; it is unclear if reasons for differences are due to known risk factors. Our study examined the association between ethnicity/race and RCD among women with one previous cesarean and whether demographic (age, marital status, education, language, and delivery year), anthropomorphic (height, prepregnancy body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Biological differences in pelvic architecture and connective tissue, labor prolongation and the likelihood of fetal compromise between ethnic groups have been proposed to explain these findings 26 . Provider bias, manifested as variation in labor practices depending on race, has also been suggested to be a contributing factor 27 . In this analysis, we provided additional insights into other ethnic groups (South Asian, Sub-Saharan and Mediterranean) living outside the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological differences in pelvic architecture and connective tissue, labor prolongation and the likelihood of fetal compromise between ethnic groups have been proposed to explain these findings 26 . Provider bias, manifested as variation in labor practices depending on race, has also been suggested to be a contributing factor 27 . In this analysis, we provided additional insights into other ethnic groups (South Asian, Sub-Saharan and Mediterranean) living outside the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focusing on the association between race/ethnicity and mode of delivery have been restricted to American populations. Black women are more likely to have failed IOL than non-Hispanic white women 23,25 and are also more likely to have repeat CS 26,27 . Biological differences in pelvic architecture and connective tissue, labor prolongation and the likelihood of fetal compromise between ethnic groups have been proposed to explain these findings 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This issue is critical, given that the majority of women undergoing LAC or elective RCB do not have a clear understanding of the relative risks and benefits of each method 7,8 . The absence of informed decision making is particularly worrisome for Latina women as they appear to have a lower likelihood of LAC success compared with non‐Latina women 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have found that Latina women value having family support and involvement in their prenatal care and that their own beliefs and experiences greatly influence their decisions 15‐17 . In either case, provider bias has frequently been proposed as a factor that may directly or indirectly influence medical discussions about mode of delivery 10 …”
Section: Introductionmentioning
confidence: 99%
“…11 The relationship of VBAC success prediction in the Latina community is particularly worthy of note, given some reported disparate findings. 11 Interestingly, whatever the complex interactions of the pelvic bony dimensions and soft tissue dynamics are, the vaginal birth statistics do not appear to show significant differences between women in different racial/ethnic groups, in the United States. 12 The use of racial identity may not therefore be statistically relevant to any of the algorithms used for successful VTOL prediction.…”
mentioning
confidence: 96%